2021
DOI: 10.1021/acs.jpcc.0c08838
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of the Atomically Precise C4 Core [Au9(PPh3)8]3+ Cluster Probed by Transient Absorption Spectroscopy and Time-Dependent Density Functional Theory

Abstract: Structural isomerism of [Au9(PPh3)8]3+ has been studied experimentally, mostly concerning the symmetry of the Au9 core. Recently, the C 4 isomer of [Au9(PPh3)8]3+ has been shown to exist in solution phase while the D 2h isomer is present in the solid state [Inorg. Chem. 2017, 56, 8319–8325]. In this work, geometric, electronic, and optical properties of C 4 [Au9(PPh3)8]3+ are investigated by using the combined second-order density-functional tight-binding (DFTB2) method and time-dependent density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 97 publications
4
15
1
Order By: Relevance
“…[ 214 ] The transient absorption study of [Au 9 (PPh 3 ) 8 ] 3+ in methanol and dichloromethane showed relatively fast S 1 relaxation decay times of 2 ps and 45 ps which were assigned to intersystem crossing (S 1 → T 1 ) and nonradiative relaxation (S 1 → S 0 ), respectively. [ 215 ]…”
Section: Properties Of Phosphine Ligated Au Clustersmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 214 ] The transient absorption study of [Au 9 (PPh 3 ) 8 ] 3+ in methanol and dichloromethane showed relatively fast S 1 relaxation decay times of 2 ps and 45 ps which were assigned to intersystem crossing (S 1 → T 1 ) and nonradiative relaxation (S 1 → S 0 ), respectively. [ 215 ]…”
Section: Properties Of Phosphine Ligated Au Clustersmentioning
confidence: 99%
“…[ 337a,338 ] While the experimental spectrum agrees with the theoretical result for [Au 8 (PPh 3 ) 8 ] 2+ , the experimental spectrum of [Au 9 (PPh 3 ) 8 ] 3+ in solution represents the alternative C 4 isomer. [ 215 ] Yao and Tsubota simulated the spectra for the two isomers of the Au 9 core using the truncated ligand PH 3 for their study of the [Au 9 (TPPS) 8 ] 5− cluster; however, due to the symmetry constraints in the simulations, the experimental spectrum was compared to the D 2h isomer as well, [ 339 ] despite the fact that the experimental crystal structure clearly shows the C 4 core isomer. [ 340 ] With the help of the experimental and electronic structure findings of Tsukuda and co‐workers, [ 55,23 ] recent work by us showed that the experimental UV–visible spectra of [Au 9 (PPh 3 ) 8 ] 3+ in both MeOH and DCM should be assigned to the C 4 core isomer (Figure 15c).…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This VSI contains 11 papers concerning MPCs, 5 of which are related to the chemical properties of MPCs: CO oxidation by a ferrocene-protected Au 8 cluster, reductive elimination of 1,3-diynes from an alkynyl-protected alloy cluster, the migration of a Pd atom within an Au MPC during CO oxidation, CO exchange in a carbonyl Ir 4 cluster, and the hydrogenation of nitroaromatics by supported Au n ( n = 19, 20, and 22) MPCs . Other topics reported include the synthesis of a new Au 5 Cu 6 alloy cluster, the controlled doping of a Cu atom to a Au-based alloy cluster, the synthesis of ultrastable Au clusters protected by sulfonic thiolates, the dynamics of the ligand layer playing a role in the MPC stability, the photoluminescence properties of Ag MPCs, and the optical properties of Au 9 MPC …”
mentioning
confidence: 99%